All the Pasha's men : - Fahmy, Khaled (Cambridge University Press, 1997)
Khaled Fahmy offers a new interpretation of modern Egyptian history and the rise of Egyptian nationalism in a theoretically informed study. Basing his work on previously neglected archival material, the author demonstrates how Mehmed Ali built up the Egyptian army to further his own ambitions rather than as a means of gaining Egyptian independence. In this way, the book challenges traditionally held views about early nineteenth-century Egypt and the role of Mehmed Ali as the founder of modern Egypt. The book will be essential reading for students of the Middle East, Ottomanists, military historians and those interested in the construction of the modern nation state.